Network forensics : privacy and security - Bijalwan, Anchit (Boca Raton : Chapman & Hall/CRC Press, 2022)
"Network Forensics: A privacy & Security provides a significance knowledge of network forensics in different functions and spheres of the security. The book gives the complete knowledge of network security, all kind of network attacks, intention of an attacker, identification of attack, detection, its analysis, incident response, ethical issues, botnet and botnet forensics. This book also refer the recent trends that comes under network forensics. It provides in-depth insight to the dormant and latent issues of the acquisition and system live investigation too"--
OCLC-licensed vendor bibliographic record.
Keywords: Computer crimes -- Investigation; Computer networks -- Security measures; Computer security; Forensic sciences; COMPUTERS / Computer Engineering; COMPUTERS / Computer Science; COMPUTERS / Cybernetics